Library and information science trends and research : Europe - Spink, Amanda; Heinström, Jannica (Emerald Group Pub., 2012)
"Library and Information Science Trends and Research: Europe", co-edited by Professor Amanda Spink and Dr. Jannica Heinstrom provides an understanding of the new directions in library and information science/management, education and research in Europe. The volume focuses on new research directions within the field but will also discuss curriculum changes due to the rapidly developing information world. Europe has developed substantially both socially and economically in the last ten years with a growing population and economy. The field of library and information science/management has also grown in educational and research developments as information increasingly has become a part of people's everyday social and life processes. This book is directly relevant to information scientists, information professionals and librarians, social scientists and people interested in understanding more about the trends and research in library and information science/management in the European region. Undergraduate and graduate students, academics, educators, and information professionals interested in library and information science will find this book of particular benefit.
Keywords: Library science -- Europe.; Information science -- Europe.; Europe.; elektronické knihy; electronic books